(f, ?)?Statistical Convergence of Order ? - Kandemir, Hacer Şengül; Et, Mikail; Çakallı, Hüseyin (American Institute of Physics Inc., 2022)
The main object of this article is to introduce the concepts of (f, ?)? statistical convergence of order ? and strong (f, ?)? summability of order ? of sequences of real numbers and give some inclusion relations between these spaces. © 2022 American Institute of Physics Inc.. All rights reserved.
5th International Conference of Mathematical Sciences, ICMS 2021 -- 23 June 2021 through 27 June 2021 -- Istanbul -- 184127
Keywords: Modulus function; statistical convergence; strong ??summability; ?? statistical convergence